Frequent nightmares and its associations with psychological and sleep disturbances in hospitalized patients with cardiovascular diseases. (17th December 2020) - Horie, Haruaki; Kohno, Takashi; Kohsaka, Shun; Kitakata, Hiroki; Shiraishi, Yasuyuki; Katsumata, Yoshinori; Hayashida, Kentaro; Yuasa, Shinsuke; Takatsuki, Seiji; Fukuda, Keiichi
Abstract: Aims: Frequent nightmares can pose a serious clinical problem, especially in association with sleep and psychological disturbances, in the general population. However, this association has not been investigated in inpatients with cardiovascular (CV) diseases. Furthermore, whether CV medications could induce iatrogenic nightmares remains unknown. In a cross-sectional designed study, we evaluated the prevalence and determinants of frequent nightmares and its association with sleep and psychological disturbances among hospitalized CV patients. Methods and results: A total of 1233 patients (mean age, 64 ± 15 years; 25.1% female) hospitalized for various CV diseases in a single university hospital were enrolled. We assessed nightmares and sleep characteristics using the Pittsburgh Sleep Quality Index (PSQI), sleep-disordered breathing (SDB) using nocturnal pulse oximetry, and psychological disturbances using Hospital Anxiety and Depression Scale (HADS). Overall, 14.8% and 3.6% of the patients had at least one nightmare per month and per week (frequent nightmares), respectively. In this cohort, 45.9% had insomnia (modified PSQI > 5), 28.0% had SDB (3% oxygen desaturation index > 15), 18.5% had depression (HADS-depression ≥ 8), and 16.9% had anxiety (HADS-anxiety ≥ 8). Frequent nightmares were not associated with CV medications and SDB but were associated with depression [odds ratio (OR) = 4.61, 95% confidence interval (CI) = 2.03–10.48], anxiety (OR = 5.32, 95% CI = 2.36–12.01), and insomnia (OR = 7.15, 95% CI = 2.41–21.22). Conclusions: Frequent nightmares were not uncommon in patients hospitalized for CV diseases. Although the cause–effect relationship is unclear, frequent nightmares were associated with psychological disturbances and insomnia, but not iatrogenic factors, among hospitalized CV patients. Cardiologists should be more conscientious to nightmare complaints with respect to screening for psychological disturbances and insomnia.